EFFECT OF FINANCIAL RATIOS TO STOCK RETURN ON COMPANIES REGISTERED AT IDX - Prayoga, Josea; Sri Wahyudi, Agustinus (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
This research has a purpose, and that is to determine the effect of return on equity, debt to equity ratio, current ratio, total asset turnover, and price to book value on stock return. This research use Mining Companies that are listed in the Indonesia Stock Exchange for the 2012–2020 period as the population. In this research, the sampling method that used is a purposive sampling method with a total of 11 companies. Causal research is implemented in this research to determine the effect between the independent variables and dependent variables. This research uses multiple linear regression to process the data. Based on the test result, Return on equity, Debt to equity, Current ratio, Total asset turnover and Price to book value does not have effect on stock return.